Sustainable Supply Chain Strategy and Sustainable Competitive Advantage: A Mediated and Moderated Model - Sun, Jianmin; Sarfraz, Muddassar; Khawaja, Kausar Fiaz; Abdullah, Muhammad Ibrahim (Frontiers in Public Health, 2022)
In the global business environment, sustainability has become a competitive priority of most enterprises. Sustainability as a differentiation approach enables organizations to compete in today's environment. However, despite the increasing adaptability to sustainability practices, pharmaceutical supply chain management is still facing challenges in preserving the global environment. The study contemplates the impact of sustainable supply chain strategy and sustainable competitive advantage while considering the mediating role of sustainable supply chain practice and moderating role of sustainability inhibitors. The data was collected from the 180 employees working in the pharmaceutical companies of Pakistan. The study applied a quantitative approach for testing a theoretical model, using discriminant validity analysis, assessment of measurement model, composite reliability & validity analysis to assess the dimensions and model's reliability and validity. The study results show a positive relationship between sustainable supply chain strategy and sustainable competitive advantage. Sustainable supply chain practice mediates the relationship between sustainable supply chain strategy and sustainable competitive advantage, while sustainability inhibitors strengthen the relationship between sustainable supply chain strategy and sustainable supply chain practice. This study will help managers develop impactful sustainable supply chain management practices that will lead to sustainable performance.